Geochemical comparison of late Mesozoic and early Cenozoic volcanic rocks in South Mongolia: Implications for petrogenesis and geodynamic evolution - Khasmaral, Togtokh; Amarjargal, Bars; Miao, Laicheng; Munkhtsengel, Baatar; Chimedtseren, Anaad (Mongolian Geoscientist, 2019)
The Mesozoic-Cenozoic volcanic rocks are widely distributed in the interior of the East Asia and document the tectonic transition of East Asia. We present new geochronology and geochemistry data of late Cretaceous-early Cenozoic basalts in Bayantsagaan and Han-Uul volcanic provinces in South Mongolia, in order to explore their petrogenesis and geodynamic settings. The volcanic rocks in the Bayantsagaan and Han-Uul field yielded K-Ar ages of 90.55±1.93 Ma and 55.49±1.49 Ma, respectively. The volcanic rocks in South Mongolia can be subdivided into to alkaline basalts and tholeiitic series, and are characterized by ocean island basalts (OIB) trace elements features, such as enrichment of light REE relative to heavy REE and enrichment in large ion lithophile elements (LILE) with positive K anomaly. Compared with the late Cretaceous, the early Cenozoic basalts show a decrease in the contents of HREE and an increase of Nb and Ta. Crustal contamination and fractional crystallization are insignificant in the genesis of late Cretaceous-early Cenozoic basalts South Mongolia. The available Sr-Nd isotope results indicate that a mixing depleted (DM) and enriched mantle (EM) signature characterize in late Cretaceous volcanic rocks, which derived from magmas from the asthenosphere with some contributions of metasomatized subcontinent lithospheric mantle, whereas the early Cenozoic basalts are ascribed to contributions from the asthenospheric mantle. We propose that the generation of the late Cretaceous-early Cenozoic volcanism (90-40 Ma) in Mongolia is probably related to the shallow mantle upwelling (asthenosphere) induced by the edge convection along the northern margin of the North China Craton (NCC), triggered by a far-field effect of Indo-Asian collision.